Potencial inseticida de plantas da caatinga sobre Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) - Sá, Jessica dos Santos (2018)
In Brazil, eucalyptus culture is of fundamental importance; due to their participation in the forest sector economy. However, homogenous plantings of the species can favor pest insects, reducing their productivity. The Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) Carpintero & Dellapé 2006, is an insect from Australia that has become an invasive pest in Eucalyptus plantations; and that it does not yet have a totally satisfactory management method. In recent years, research has shown that essential plant oils with insecticidal effects are an alternative to pest control. The Brazilian flora stands out for its biodiversity of plant species that present bioactive substances. That way, the present study aimed to evaluate the insecticidal activity of essential oils of Lippia sidoides, Croton tetradenius and Croton grewioides, on adults and nymphs of the bronze-bug. The experiment was carried out at the Forest Entomology Laboratory (LEFLO), located at the Federal University of Sergipe (UFS), in an air conditioned room, with temperature of 25 ± 1 °C and photo phase of 12 hours. The experimental design was completely randomized. Adult and nymphal bioassays were sprayed with 2mL of the solutions of the three essential oils. For each oil, different concentrations (0, 5, 10, 15 and 20%) were tested with five replicates, each containing 10 insects, totaling 250 individuals. The effect of the action (CL50 and CL90), 24 hours after the applications, was evaluated where bedbugs that did not move after stimulation were considered dead. The essential oils of L. sidoides, C. tetradenius and C. grewioides acted quickly on the insects. In the toxicity test, the mortality of 90% of T. peregrinus, after contact with essential oil of the three species studied, at a concentration of 20%, on adults and nymphs was verified. Already the lethal concentrations required to kill 50% ranged from 5 to 15%. The concentrations of 15 and 20% of the solutions provided higher mortality, being the most promising for pest control. Therefore, it is concluded that essential oils of Lippia sidoides, Croton tetradenius and Croton grewioides demonstrate insecticidal potential on adults and nymphs of Thaumastocoris peregrinus.